The Human Immunodeficiency Virus Coat Protein gp120 Promotes Forward Trafficking and Surface Clustering of NMDA Receptors in Membrane Microdomains - Xu, Hangxiu (Society for Neuroscience, 2011)
Infection by the human immunodeficiency virus (HIV) can result in debilitating neurological syndromes collectively known as HIV-associated neurocognitive disorders. Although the HIV coat protein gp120 has been identified as a potent neurotoxin that enhances NMDA receptor function, the exact mechanisms for this effect are not known. Here we provide evidence that gp120 activates two separate signaling pathways that converge to enhance NMDA-evoked calcium flux by clustering NMDA receptors in modified membrane microdomains. gp120 enlarged and stabilized the structure of lipid microdomains on dendrites by mechanisms that involved a redox-regulated translocation of a sphingomyelin hydrolase (neutral sphingomyelinase-2) to the plasma membrane. A concurrent pathway was activated that accelerated the forward traffic of NMDA receptors by a PKA-dependent phosphorylation of the NR1 C-terminal serine 897 (masks an ER retention signal), followed by a PKC-dependent phosphorylation of serine 896 (important for surface expression). NMDA receptors were preferentially targeted to synapses and clustered in modified membrane microdomains. In these conditions, NMDA receptors were unable to laterally disperse and did not internalize, even in response to strong agonist induction. Focal NMDA-evoked calcium bursts were enhanced by threefold in these regions. Inhibiting membrane modification or NR1 phosphorylation prevented gp120 from accelerating the surface localization of NMDA receptors. Disrupting the structure of membrane microdomains after gp120 treatments restored the ability of NMDA receptors to disperse and internalize. These findings demonstrate that gp120 contributes to synaptic dysfunction in the setting of HIV infection by interfering with NMDA receptor trafficking.